Analisis Cemaran Mikroba Escherichia Coli Pada Bumbu Lumpia di Wilayah Pantai Desa Sanur Kaja Denpasar Selatan - Adnyani, Ni Kadek Mita Dwi; Agustini, Ni Putu (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
Based on the BPOM RI report in 2019, there were 373 cases of food poisoning in Bali, with 43 cases of processed food poisoning. One of the processed snacks that are often found in tourism areas is spring rolls. Lumpia is served together with the seasoning which is made from peanuts with high protein and water content so that if it is not processed properly it can facilitate the growth of bacteria, one of which isEscherichia coli. The purpose of this study was to determine the food safety of spring roll seasoning sold by traders in the Pantai area of Sanur Kaja Village, South Denpasar. Observational analytic research type with designcross sectional and sampling techniquesPurposive Sampling with 16 samples of spring roll traders. Assessment of food safety scores, TPC, MPN and TPC testing was carried out Escherichia Coli so as to get the results, namely, 11 samples (68.7%) with the vulnerable category, but safe for consumption. The total microbial contamination was above the maximum limit, namely 3 samples (18.8%), bacterial contaminationcoliform above the maximum of 11 samples (68.8%) and there was 1 sample (6.2%) positive for bacteria Escherichia Coli. Based on the results of the Kruskal Wallis test, it was concluded that there was a difference between total microbial contamination and contamination Escherichia Coli bacteria with a value-based food safety scoreAsymp. sig 0.05. So it can be concluded that the food safety of spring roll seasoning sold in the Pantai Desa Sanur Kaja area is categorized as vulnerable, but safe for consumption.Keywords: Spring Roll Seasoning, Food Safety Score, Total Microbial Contamination, Coliform Bacteria Contamination, Escherichia Coli.